2015
DOI: 10.1155/2015/429253
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pLG72-Induced Oxidative Stress Using Systemic Approaches

Abstract: G72 is a schizophrenia-susceptible gene encoding a polypeptide with 153 amino acids. In 2002, it was originally proposed as an activator of D-amino acid oxidase (DAOA) that could enhance the activity of DAAO and subsequently reduce the neurotransmission of N-methyl-D-aspartate receptors. However, several controversial findings have been reported recently. Due to a number of inconsistent descriptions of pLG72's biofunctions, this study aims to identify the cellular effects induced by pLG72 in U87 cells using sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…In addition to genetic studies, reduced d -serine levels in cerebrospinal fluid and serum have been reported (35,36). Moreover, in addition to the role of G72 protein in glutamate functions, pLG72 has also been considered to play an important role in oxidative stress (12). It has been well established that the levels of reactive oxidants were increased in patients with schizophrenia compared with healthy subjects (3743).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to genetic studies, reduced d -serine levels in cerebrospinal fluid and serum have been reported (35,36). Moreover, in addition to the role of G72 protein in glutamate functions, pLG72 has also been considered to play an important role in oxidative stress (12). It has been well established that the levels of reactive oxidants were increased in patients with schizophrenia compared with healthy subjects (3743).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Sachchi et al (11) reported that pLG72 inhibited DAAO activity. Recently, Wang et al (12) investigated the role of pLG72 in oxidative stress and concluded that pLG72 may represent an aetiological factor in neurological and psychiatric disorders via the enhancement of mitochondrial reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its role in modulating DAAO, pLG72 is also a mitochondrial protein that regulates the production of reactive oxygen species 34 . A cell line study using systemic approaches indicated that pLG72 might be involved in the induction of ROS 35 . Another study found that pLG72 interacted with a mitochondrial protein (methionine-R-sulfoxide reductase B2) that functioned in oxidative stress defense 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a role of pLG72 in the induction of oxidative stress was also proposed by a transcriptomics analysis (Wang et al, 2015 ). Accordingly, these authors reported an increase in the reactive oxygen species (ROS) by 69% in U87 cells overexpressing pLG72: induction of ROS was quenched by adding a scavenger such as Tempol.…”
Section: Introductionmentioning
confidence: 95%
“…Accordingly, these authors reported an increase in the reactive oxygen species (ROS) by 69% in U87 cells overexpressing pLG72: induction of ROS was quenched by adding a scavenger such as Tempol. Following pLG72 overexpression, the transcriptomics profile identified six genes involved in signal transduction ( RTN1, CNTD2, MAP4K4, HIPK3, TRIM40 , and SAG ), six genes participating in calcium binding and secondary messenger transduction ( GALNT3, TBC1D8B, SCUBE2, SMOC2, EDNRA , and PLA2G5 ), and eight genes classified as nucleotide-binding proteins ( HNRNPCL1, FOXR2, ADAL, MAF, UPP1, ARL8A, NR2C1 , and PSMA1 ) (Wang et al, 2015 ). Concerning the top gene ontology term in biological processes, pLG72 might increase the production of oxidative stress via hydrogen peroxide production and might be involved in nitric oxide biosynthesis/metabolism and in the arginine metabolic process (Wang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%